Cortázar and reworking mythemes in “Throat of a Black Kitten" - Ramírez, Diana (2018)
This work is a mitocritical approach to Julio Cortazar’s short story, "Throat of a Black Kitten". The purpose of this study is the female character because there is a contrast with other texts in the work of the Argentine author when he uses mythemes like Labyrinth and the Minotaur. "Throat of a Black Kitten" is a change in the meaning of symbols, since femininity gives a different nuance and confers a crucial change for symbols, as it is not the figure of the male monster of ancient Greece, but a figure that recalls the primal instinct invested in this, whose power lies in its duality, its monstrous character.